OPTIMIZATION OF THE WELDING PROCESS FOR GRADE S-135 PIPELINE: IMPACT ON MECHANICAL PROPERTIES UNDER AWS D1.1”, SU TRADUCCIÓN EN ESPAÑOL ES: “OPTIMIZACIÓN DEL PROCESO DE SOLDADURA PARA TUBERÍA GRADO S-135: INCIDENCIA EN PROPIEDADES MECÁNICAS BAJO AWS D1.1 - Ibañez Solis Lenin Edwin (2025)
The demand that exist in the field of donation of used oil pipelines by oil companies to public entities in Ecuador, created the need to investigate which is the best welding process that can be adapted to the type of material, this article evaluated the mechanical behavior of the welded joint of oil pipeline S-135 under the welding code AWS D1.1 that, by means of tensile tests it was determined, which is the tensile strength of the welded joint, with different welding process such as the SMAW process (Shielded metal arc welding) and FCAW (Fluxed cored arc welding), for the welding joints of the SMAW process was used filler material such as electrodes E-7018 and E-8018, with heating and post-heating temperatures according to the equivalent carbon percentage of the material, for this the spark test was carried out and the chemical composition of the material was determined. For the FCAW welding process. The Charpy test (CVN) was carried out to determine the material’s toughness, in other words the resistance to impact energy absorption. To evaluate the welded joint, non-destructive tests such as Penetrant Ink and Ultrasound were carried out, and in this way the welded joint was evaluated in a superficial and subsurface manner. Tit was concluded that the welding process for the S-135 pipeline used is the SMAW process using E7018 filler material as root pass and filler, this process turned out to be the most efficient.